Understanding Bullying and Cyberbullying Through Video Clips on Social Media Platforms - Jadán-Guerrero, Janio (2023)
Bullying and cyberbullying are widely recognized as complex problems that have serious negative repercussions for the health and society of children and adolescents. Bullying can take place in-person at school, home or work, irrespective of age, gender, or role. Cyberbullying can take place on messaging platforms, social media platforms, gaming platforms, or marketing platforms. For example, posting embarrassing photos or videos of someone on social media sending hurtful or spreading lies, as well as abusive or threatening messages, images, or videos through messaging platforms. Offenders impersonate someone and send malicious messages to others in their name or through fake accounts. In this sense, the use of short videos based on the principles of microlearning is scented as a proposal to understand and prevent bullying and cyberbullying. The objective of this article is to analyze how video clips are used on social platforms to raise awareness of bullying and cyberbullying and to propose the creation of new video clips as resources for an awareness-raising MOOC. The methodology followed a phase of analysis of videos on the TikTok and YouTube networks, in order to have a baseline prior to the creation of new video clips by twelve students of the Digital Design and Multimedia career. The content of the videos was evaluated by a psychologist to finally select the appropriate ones for a marketing campaign of an awareness MOOC.